2019
DOI: 10.1038/s41386-019-0438-0
|View full text |Cite
|
Sign up to set email alerts
|

Aging mice show impaired memory updating in the novel OUL updating paradigm

Abstract: Memories do not persist in a permanent, static state but instead must be dynamically modified in response to new information. Although new memory formation is typically studied in a laboratory setting, most real-world associations are modifications to existing memories, particularly in the aging, experienced brain. To date, the field has lacked a simple behavioral paradigm that can measure whether original and updated information is remembered in a single test session. To address this gap, we have developed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(87 citation statements)
references
References 68 publications
(107 reference statements)
5
68
1
Order By: Relevance
“…For example, we have previously shown that OLM is impaired in 18‐month‐old C57BL/6J mice (Kwapis et al., ). In order to study memory updating in these mice, we increased the amount of training from one 10‐min session to three 10‐min sessions (one session per day for 3 days) and verified that old mice successfully learn the original object locations under this increased training protocol (Kwapis et al., ). If necessary for a particular age or strain, the training protocol could be additionally modified by lengthening the training session or increasing the number of training sessions to ensure acquisition of the training information.…”
Section: Commentarymentioning
confidence: 88%
See 4 more Smart Citations
“…For example, we have previously shown that OLM is impaired in 18‐month‐old C57BL/6J mice (Kwapis et al., ). In order to study memory updating in these mice, we increased the amount of training from one 10‐min session to three 10‐min sessions (one session per day for 3 days) and verified that old mice successfully learn the original object locations under this increased training protocol (Kwapis et al., ). If necessary for a particular age or strain, the training protocol could be additionally modified by lengthening the training session or increasing the number of training sessions to ensure acquisition of the training information.…”
Section: Commentarymentioning
confidence: 88%
“…We have shown that OUL is hippocampus dependent and, like OLM, is acutely sensitive to manipulations in dorsal CA1 (Kwapis et al., ). We have also confirmed that the update session in OUL engages the original memory, rather than forming a new, discrete memory (Kwapis et al., ).…”
Section: Commentarymentioning
confidence: 96%
See 3 more Smart Citations